Ensino de artes visuais e cultura periférica: reflexões a partir da Escola Municipal Frei Afonso no baixo Roger, João Pessoa, PB - Salustiano, Carlos Eduardo (2017)
The present research sought to comparatively analyze the images and artifacts produced by the Frei Afonso Municipal School students, located in Baixo Roger, in the city of João Pessoa - PB, in Visual Arts classes and outside them, with the cultural references of the place where live and with their aesthetic daily life. The research was qualitative, exploratory and as a methodological procedure the formation of a participatory focal group. The paths followed to reach the main objective of this research included the contextualization of students' cultural references. Documentary data of the educational institution were analyzed as the Political Pedagogical Project and the School Regiment. Images and objects produced by the students in the Arts classes were investigated and a cultural mapping of Baixo Roger was carried out with the focus group, where most of the students live. In order to arrive at these data, I counted on the following collection instruments: application of questionnaires, interviews, testimonials, photographic and audiovisual documentation. The research seeks to answer the following problem: Does Frei Afonso Municipal School address the aesthetics of Baixo Roger's daily life and of students in the Visual Arts curriculum? The theoretical basis was based on authors who contributed to the discussions necessary for the formation of the central concepts of work: concept of periphery and favela, their histories, characteristics, differences and current challenges (Moura and Ultramari, Denaldi, Zaluar and Alvito); Concept of culture and art of the periphery (Hollanda, Frota, Tavares); Aesthetics of daily life (Richter, Barbosa); Curriculum issues (Silva, Giroux and Simon); History and philosophical concept of multiculturalism (Semprini); And the contribution of multiculturalism in education and in the visual arts teaching(Candau, Canen, Barbosa).